Industrial revolution 4.0 career agility and competencies among secondary school counsellors in preparing students future skills in Malaysia - Balan, Subash; Nor Zainudin, Zaida; Abd. Jalil, Habibah (Macrothink Institute, 2022)
Intro Industry 4.0 is transforming how businesses operate by integrating enabling technologies, such as the internet of things (IoT), artificial intelligent (AI), cloud computing, autonomous robots, simulation, analytics, additive manufacturing and machine learning, into their manufacturing facilities, overall operations, or on how they provide their services. Smart factories combine cutting-edge sensors, embedded software, and robots to gather and analyse data, enabling improved decision-making via more predictive analyses. This current technological transformation of industrial revolution 4.0 changes our education system in an indirect way to meet industrial needs. Future careers are changing accordingly. Counselors in schools play an important part in ensuring that students are adequately prepared to adapt to changing work environments and maintain their relevance in the labour market. It is very likely that guidance counsellors in schools are not prepared for or aware of the future careers that will be available in the job market as a result of Industrial Revolution 4.0. Objective This study is to measure the level of the school counselor's competencies and career agility in preparing secondary school students for IR4.0 future skills. Method An online survey questionnaire with 44 items was used to collect data. 80 secondary school counsellors completed the online survey. Finding show that the counsellor’s competencies and career agility of counselors in the aspect of preparing secondary school students towards future skills is at a moderate level. Conclusion, the accountable party needs to do what needs to be done to raise school counsellors' familiarity with IR4.0. As a result, school counsellors will be better able to incorporate IR4.0 principles into their guidance and counselling as well as their coaching practises, resulting in graduates who are well-equipped to meet the needs of the industries of the future.